Epithelial and stromal metabolite changes in the transition from cervical intraepithelial neoplasia to cervical cancer: an in vivo 1H magnetic resonance spectroscopic imaging study with ex vivo correlation. - De Silva SS; Payne GS; Morgan VA; Ind TE; Shepherd JH; Barton DP; Desouza NM; De Silva, Sonali S; Payne, Geoffrey S; Morgan, Veronica A; Ind, Thomas E J; Shepherd, John H; et al. (European Radiology, 2009)
To investigate epithelial and stromal metabolite changes in cervical intraepithelial neoplasia (CIN) and cervical cancer in vivo and correlate findings with MR spectroscopy of tissue samples. Forty-seven women (19 with CIN, 28 with cervical cancer) underwent endovaginal MR at 1.5 T with T2-W and localised 2D MR spectroscopic imaging (PRESS, TR = 1,500 ms, TE = 135 ms). tCho, 2 ppm and -CH(2) lipid peaks were measured in epithelial (>50% epithelium, no tumour), stromal (>50% stroma, no tumour) and tumour (>30% tumour) voxels. Unsuppressed water signal from the same voxel provided a concentration reference. (1)H HR-MAS MR spectra were acquired from tissue in 37 patients (11.74 T, pulse-acquire and cpmg sequences, with water pre-saturation). Analysable data from 17 CIN and 25 cancer patients showed significant increases in tCho (p = 0.03) and 2 ppm (p = 0.007) in tumour compared with epithelial voxels from CIN patients, but not with epithelial voxels from cancer patients. No significant differences were seen in stroma from cancer compared with CIN patients. Differences in -CH(2) lipids were not significant between groups. There was no significant correlation between in vivo and ex vivo tCho or -CH(2) lipids. Estimated in vivo concentrations of tCho and 2 ppm resonances increase in tumour and adjacent epithelium in progression from CIN to cervical cancer.